THE ROAD TO DOTCALM IN EDUCATION - Milliron, Mark David (Online Learning, 2004)
The DotCom era has educators running faster and faster to keep up with technology that feels more and more elusive. This paper recognizes this chase for what it is—educationally hazardous—and suggests that if we continue racing ahead, we are at risk for personal and professional crashes. Based on the work of the League for Innovation in the Community College with hundreds of colleges through conferences and consultations, this paper shares individual, organizational, and societal road hazards that have proven challenging on this road. The paper concludes with a vision of a journey toward DotCalm, with a focus on learning and inclusiveness in our technology and education adventures.